Exploring the relationship between new bank debt and earnings management: Evidence from Italian SMEs - Riccardo Palumbo; Pierangelo Rosati (Economies, 2022)
This paper investigates the relationship between bank debt and earnings management in private SMEs in a bank-oriented economy. In this study, we leverage a sample of 4866 Italian private SMEs from 2005 to 2012 and propose a new metric to isolate the annual increase in bank debt. The results of our OLS regression suggest that, even though bank monitoring is an effective mechanism to constrain firms' earnings management, firms engage in higher income-increasing earnings management, as proxied by discretionary accruals, in the fiscal year prior to a new bank loan application. The results are robust to different econometric specifications and are not affected by endogeneity.
Keywords: 330; bank debt; bank monitoring; earnings management; financial reporting